The experience of scar management for adults with burns: An interpretative phenomenological analysis. Issue 6 (September 2016) - Martin, C.; Bonas, S.; Shepherd, L.; Hedges, E.
Highlights: Scar management treatments pose a range of perceived benefits and challenges. Patients stay positive, hide or explain treatment, and use social support to cope. Treatments may become integrated into patient identities, body image and routines. Patients may rely on the perceived protection and containment of pressure garments. Treatments can adversely affect social experiences. Abstract: Burns can have both physical and psychological effects on individuals. Pressure garments and silicone gels are used to improve the aesthetic appearance and functions of the skin, but these treatments have been associated with various physical, emotional, sexual and social difficulties. Interpretative phenomenological analysis (IPA) was used to explore participants' experiences of scar management. IPA examines individual experiences before comparing results across cases, and is suited to capture the different ways in which individuals experience a phenomena as well as cautiously looking at patterns across cases. Eight burn patients who had experienced scar management, including pressure garments, were interviewed. Two superordinate themes were identified: Assimilation of Pressure Garment Identity, and Psychosocial Functions of the Pressure Garments. The findings offered insight into the positive and negative experiences of scar management, describing the diverse personal and social functions of the pressure garments and how they became integrated into participants' identities. By understanding the individual nature of these experiences, healthcare professionals can enhance support around these issues and potentially aid adherence to treatment. Further research with different demographic groups as well as for other burn treatments would be useful to develop and contextualise these findings.